2023
DOI: 10.1371/journal.pone.0292259
|View full text |Cite
|
Sign up to set email alerts
|

Land finance, infrastructure investment and housing prices in China

Mengkai Chen,
Ting Chen

Abstract: Housing prices in China have experienced rapid growth in recent decades, and land finance has long been discussed as an important factor in this growth. In this paper, we explore the interactions among housing prices, land transfer revenue and infrastructure investment from the perspective of government revenue and expenditure. Based on the panel data of 35 large and medium-sized cities in China from 2000 to 2017, the empirical results show that land transfer revenue, infrastructure investment and housing pric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Typically, local governments adopt the strategy of granting industrial land at low prices and commercial land at high prices. Specifically, local governments offer industrial land at low prices to attract commercial investment and offer commercial land at high prices to compensate for the loss of fiscal revenues caused by industrial land concessions, which is far below the cost of compensation for agricultural land, and they also invest more of the proceeds from land concessions in productive expenditures, such as infrastructure [37]. Although this strategy has contributed to the rapid economic development of cities, it has also had many adverse effects on UIQ.…”
Section: Research Hypothesismentioning
confidence: 99%
“…Typically, local governments adopt the strategy of granting industrial land at low prices and commercial land at high prices. Specifically, local governments offer industrial land at low prices to attract commercial investment and offer commercial land at high prices to compensate for the loss of fiscal revenues caused by industrial land concessions, which is far below the cost of compensation for agricultural land, and they also invest more of the proceeds from land concessions in productive expenditures, such as infrastructure [37]. Although this strategy has contributed to the rapid economic development of cities, it has also had many adverse effects on UIQ.…”
Section: Research Hypothesismentioning
confidence: 99%
“…Prior studies have consistently demonstrated the significant influence of Feng-shui features on housing prices. Chen (2005), for instance, investigated land consolidation in Taichung and found that road-facing land experienced a depreciation effect. Conducting a regression analysis exclusively on residential areas, Chen (2005) observed that facing-road-clash had an even more pronounced impact on the discount rate of residential land.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Chen (2005), for instance, investigated land consolidation in Taichung and found that road-facing land experienced a depreciation effect. Conducting a regression analysis exclusively on residential areas, Chen (2005) observed that facing-road-clash had an even more pronounced impact on the discount rate of residential land. On average, land with road-facing attributes exhibited a discount rate of 10%, while residential land with signs of facing-road-clash had an average discount rate of 14%.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation